Information Systems: what kind of science is this? (Journal of Information Systems and Technology Management, 2005)
Information Systems (IS) is a field of study concerned with a large range of multifaceted issues regarding the development, use and implications of information and communication technologies in organizations. It is a recent field of study, yet not well understood by academics and professionals of other areas, even in the fields related to IS such as management and operational research. In this work written for academics and professional, an attempt is made to present some thematic areas of IS, theoretical foundations and some methodological and institutional characteristics. Information Systems is a fragmented field that does not use the methodological rigor usually associated with other scientific disciplines, but has given origin to an impressive wealth of knowledge in the organizational level.